Democratização da cultura nas bibliotecas infanto-juvenis - Madalena Sofia Mitiko Wada (1985)
The present work intended to find out, according to the liberal ideology, whether libraries for children and young people in são Paulo City accomplish the democratic ideal of access to culture. For this, we selected a sample of nine libraries from a total amount of twenty four. Employees of these libraries were interviewed (partially structured interview) . This technique was chosen because it was considered the most appropriate for the present research, as an exploratory study tool. This guaranteed a collection of data of real interest for the researcher,as well as a chance for the interviewed people to furnish further data. Thus, the answers have been object of content analysis. The interviews have revealed that: 1 - There are factors, as location and work schedule in the libraries, that prevent the access from certain segments of the society; 2 - Although not preventing access, there áre other factors, as the absence of employees and prejudice on their part, size of the library collection, altogether leading to a differentiated áttendance. These differences are directly linked to social class differencesi 3 - The public libraries' explici t goals do not emphasize any of the following functions: education, information, culture and leisure. Yet, in practice, a greater emphasis is assigned to the educational function. This is due to those libraries' conscious option which is aggravated by unappropriate working conditions; 4 - As to their performance, libraries for children and young people in são Paulo City constitute simple appendices to schools. In other words, they play - badly - the role of school libraries, which practically do not exist in our country; 5 - Besides furnishing the information requested by children, those libraries disclose an ideology that, as the answers revealed, is the ideology of dominant classes. Thisway, they convey only values as order, discipline ,gocd tehavior, controloThus, we concluded that libraries for children and young people in são Paulo City attend precariously their users which are constituted mainly by children and young people, who use those libraries in order to accomplish school duties. As a conclusion we pointed out the need for these libraries to think over their roles. It was suggested that it is necessary to improve the professional education of librarians, sinceexisting courses do not give them the least pedagogic kriowledge required at school libraries. The full attainment of the ideal of cultural democratization in public 'libraries has not been confirmed in thisstudy. Yet, such an ideal remains valid, since it has been detected that they play the contradictory role of r~producting the dominant ideology and simultaneously transforming it. This conclusion should be object of further investigations, although the results of this study may be generalized to other public libraries of this country, whenever social-econanicconditions are similar.